Potential pharmacological effect of Quercetin Phytosome™ in the management of hyperuricemia: results from real-life clinical studies - Di Pierro, Francesco; Rabbani, Fazle; Tareen, Meherullah; Nigar, Roohi; Khan, Amjad; Zerbinati, Nicola; Tanda, Maria L.; Cazzaniga, Massimiliano; Bertuccioli, Alexander; Falasca, Paolo; Damiani, Gabriele; Villanova, Nicola (Frontiers in Nutrition, 2025)
BackgroundHyperuricemia is associated with several metabolic and cardiovascular disorders, and traditional treatments, such as xanthine oxidase (XO) inhibitors, often have limitations, such as severe hypersensitivity reactions or ineffectiveness in achieving target serum urate levels in some patients. Quercetin, a naturally occurring flavonoid, has shown potential as a hypouricemic agent through XO inhibition.ObjectiveThis study aims to evaluate the potential hypouricemic effect of Quercetin Phytosome™ (QP) supplementation across three cohort studies involving healthy adults with various metabolic health profiles, exploring its potential as a safe, effective intervention for hyperuricemia.MethodsClinical data collected in various clinics in Italy between September 2021 and April 2024 under real-life clinical settings from three distinct cohort studies, were analyzed. Cohort 1 consisted of 164 healthy participants (87 QP-treated, 77 probiotic Streptococcus salivarius (S. salivarius) K12-treated) who were monitored for 90 days. Cohort 2 included 22 mildly hyperuricemic adults with metabolic disorders receiving QP, while Cohort 3 comprised 64 obese adults with hypercholesterolemia, further divided into moderately hyperuricemic QP-treated group (n = 20), a moderately hyperuricemic Berberine Phytosome™ and monacolins (BM)-treated group (n = 22), and a normouricemic BM-treated group (n = 22). QP was administered at 400 mg of quercetin daily in all cohorts. Primary endpoints were reductions in serum uric acid levels, while secondary outcomes included effects on lipid profile, glycemia, liver enzymes, and treatment tolerability.ResultsIn Cohort 1, QP significantly reduced uric acid levels by 15.2% in males and 13.8% in females, with no significant changes observed in the probiotic group. Cohort 2 showed a significant 13.1% reduction in uric acid (p < 0.01) and a concurrent 10.2% reduction in triglycerides (p < 0.05). In Cohort 3, QP led to a 13.7% decrease in uric acid and a 20.8% reduction in triglycerides (p < 0.01), with no significant uric acid changes in the BM-treated group. QP was well tolerated across all cohorts, with minimal, transient side effects.ConclusionQP supplementation demonstrates a significant hypouricemic effect. Additionally, triglyceride-lowering benefits were evident, particularly in metabolically compromised individuals (Cohorts 2 and 3), where these effects were statistically significant. With high tolerability, these findings highlight Quercetin Phytosome™'s potential as a safe adjunctive therapy for hyperuricemia management, meriting further investigation in larger, randomized trials to confirm its efficacy and safety.Clinical Trial Registrationclinicaltrials.gov, identifier NCT06652035.